Fish pond turbidity in Cambodia - Hean Vuthana; Edwards, Peter; Szyper, James P.; Yakupityage, Amararatne; Sununtar Setboonsarng; The Swedish International Development Authority (SIDA) (Bangkok : Asian Institute of Technology, 1995)
Turbidity has been a major problem in promoting the development of small-scale aquaculture in Cambodia. It discouraged the farmers from fish pond culture. The study was divided into field work in Cambodia and laboratory work in AIT. Field work was conducted to identify factors associated with turbidity in fish ponds and to take water and soil samples. Field surveys included a preliminary survey of the whole of Svay Rieng province, farmer interviews, pond observations, and water and soil sampling. Thirty four farmers were interviewed in depth, 10 under the P ADEK program located on light gray agricultural soils in Romeas Hek district, and 14 and 10 farmers under the AIT Aquaculture Outreach program located on light gray and gray agricultural soils, respectively, in Svay Rieng district. High turbidity was mainly associated with the nature of pond soil. Pond management and specific pond inputs were identified as important factors to achieve removal of turbidity in fish ponds. Soil samples were analyzed in the laboratory to evaluate soil properties associated with turbidity. Nine experiments with nine different soil samples and with six treatment materials (quicklime; alum; salt; a combination of quicklime-alum; sub sua, a local herbaceous plant; and cow manure) were carried out in duplicate indoors in 1.5 L plastic containers to evaluate required dosages to remove turbidity from experimental turbid waters prepared by mixing soil samples with distilled water. Each material was run with a series of five dosages. All chemicals were able to remove 100% of the turbidity but high loading rates of cow manure and sub sua discolored the water due to chlorophyll. Dosage of chemical material depended on the amount of turbidity to be removed. Quicklime, alum, and a combination of quicklime-alum were good coagulants but salt was less effective. Quicklime treatment increased alkalinity rapidly, alum increased acidity rapidly, but a combination of quicklime-alum increased alkalinity only slightly with increasing dosage. Quicklime was the best material which should be recommended to farmers in Cambodia to remove turbidity in fish ponds. The required dosage of treatment materials used to remove turbidity in the range of 628 - 2846 FNU in experimental turbid water could be estimated by linear regression equation Y = a X + b, for quicklime RD = 0.037 TR + 29.40 where RD is the required dosage of quicklime (mg/I) and TR is the turbidity to be removed (FNU). This equation may be used for trial dosages to remove turbidity which may be vary from pond to pond because of different composition of water. The required dosage obtained from this study should be tested with pond water prior to recommendation to farmers in Cambodia
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science, School of Environment, Resources, and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1995
Keywords: Fish ponds -- Cambodia